A FIGURA DA MULHER COMO MÃE EM CONTOS DE MACHADO DE ASSIS - SUÉLLEN SILVA VARELA (2020)
This work seeks to analyze the figure of the female character, more specifically the role of the woman as "mother", in tales by Machado de Assis, being: “O Segredo de Augusta” (1870), “O caminho de Damasco” (1871), “A herança” (1878), “Pai contra mãe” (1906). For this, we will try to show, through analysis, the importance of this figure for the selected plots, the representation of it sensitivity and it strength, because the characters who exercise this function in the texts are women who resist to all the obstacles that are imposed by the society of the time. It is important to observe that the authority that this female figure exercises on her children, even if behind the father figure, remains strong and of fundamental importance for all the outcomes of Machado's plots addressed. It is extremely relevant for the development of the research, to consider the social context of the time, since it is projected on the plots and, for this, we approach authors such as Leite (1984), Wanderley (1996) and Candido (2004), among others present in the references. Furthermore, we also resort other authors to support aspects and concepts to be explored, such as Elisabeth Badinter (1985), on the myth of maternal love, and Luiz da Costa Lima (1981), on the concept of representation. This research seeks to show that in the selected texts motherhood is a social function and, therefore, can be exercised by other people, beyond the biological mother. This broad aspect of the function of motherhood in the narratives reveals, well beyond the positive side, also the dark side, the feelings of rejection and the no obligation in existence of love between mother and child. In addition, important aspects in the narratives are the consequences of the decisions made, based on the advice given by these female voices, the submissions that are accepted by them in order to protect their “children” and, at the same time, the power they have over them.